2004
DOI: 10.1046/j.1540-8167.2004.04352.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Predictors, and Mortality Significance of the Causative Arrhythmia in Patients with Electrical Storm

Abstract: VF is the causative arrhythmia for a sizable proportion of patients with ES. The initial ICD indication, coronary artery disease, and amiodarone therapy are predictors of the causative arrhythmias in ES. There does not appear to be any mortality difference between ES patients with VT and VF, but mortality is increased in patients with ES versus control ICD patients without ES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
2
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(102 citation statements)
references
References 25 publications
3
92
2
3
Order By: Relevance
“…Among patients whose ICDs were placed for prior VT, 64% of ES episodes were caused by VT compared to only 28% by VF. For those patients whose ICDs were placed for prior VF, 45% of ES episodes were caused by VF and only 14% by VT. 20 Analysis of MADIT II patients with electrical storm revealed similar findings. Of 12 patients who had a prior episode of VT, 11 subsequently had VT as their initial rhythm in their ES.…”
Section: Arrhythmias and Icd Therapies During Electrical Stormmentioning
confidence: 75%
See 3 more Smart Citations
“…Among patients whose ICDs were placed for prior VT, 64% of ES episodes were caused by VT compared to only 28% by VF. For those patients whose ICDs were placed for prior VF, 45% of ES episodes were caused by VF and only 14% by VT. 20 Analysis of MADIT II patients with electrical storm revealed similar findings. Of 12 patients who had a prior episode of VT, 11 subsequently had VT as their initial rhythm in their ES.…”
Section: Arrhythmias and Icd Therapies During Electrical Stormmentioning
confidence: 75%
“…Lack of a consensus definition for ES, as well as differences in ICD implant indications, concomitant medical therapy, and follow-up periods all contribute to the disparate reported incidence rates of 10-60% in the secondary prevention population. Using the definition of >/= 3 VF/VT episodes in 24-hours requiring device intervention, the incidence of ES is approximately 10-28% over a 1-3 year follow-up period when ICDs are placed for secondary prevention of cardiac arrest 1,2,8,[10][11][12][13][14][15][16][17][18][19][20][21] . From a more consistent study population in the Multicenter Automatic Defibrillator Implantation Trial II (MADIT II), the reported incidence of electrical storm in a primary prevention ICD population is substantially lower at 4% 13 18 The reported 70% identification of an acute cause in this series is disparate from the larger published trials but does point out the need to take a thorough history when presented with a storm patients to effectively treat the current storm episode and prevent further ES.…”
Section: Incidence and Timing Of Esmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of large clinical trials show that the ES developed in ICD patients may be a strong predictor of arrhythmic and nonarrhythmic death, and also rehospitalization [7,8,11,23,24].…”
Section: Pathomechanismmentioning
confidence: 99%